THE EFFECT OF IMAGE AND SERVICE QUALITY ON CUSTOMER COMMITMENT WITH TRUST MEDIATION (A Study at PUSKESMAS In-Patients, Jakenan, Regency of PATI) - R.A. Marlien; Alimuddin R R; Ali Muslihin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
Community health center as a community health service center has an important value in building a healthy and productive society. The existence of in-patient service at a public health center has been highly expected by the public who suffer from illnesess. The general public expects the nearest health center to resolve arising issues related to their illnesses. The purpose of this study was to test the effect of the Image and the Service Quality on Customer Commitment with Trust mediation. The data compiled were analysed by Linear Regression. The findings show that the Image and Service Quality significantly show a direct effect to Trust and Customer Commitment, but the Trust variable do not mediated Image and Customer Commitment. The majority of in-patients are farmers and they are more likely to feel safe and confident when treated in health centers.